(untitled) (American Journal of Islam and Society, 1987)
Since the beginning of decolonization in Africa in the late 1950’s Arab countries have found it necessary to re-establish links with Africa south of the Sahara. An Arab leader like Gamal Abdel Nasser argued in his Philosophy of the Revolution (1954) that Africa constitutes the second circle in Egypt’s three concentric circles of identity. The other two were the Arab and the Islamic. Nasser’s preoccupation with what he and his fellow Arab nationalists called the “Israeli menace”, was another factor which drove him to seek allies and friends in Africa. But Nasser was not the first Arab leader to establish close relations with the Africans. The Magrebians and the Arabians to the east also forged links with Africa in the years before the primacy of Europe in African political life. The book under review is one of a series of studies that have come out in the last decade. What distinguishes this work from those before it is its focus and its authors. In the early 1970’s when the Afro-Arab caravan began to move rapidly along the pathways of international politics, many Western and Third World intellectuals and scholars began to examine the nature of what was then believed by many as a new phenomenon in international politics. Africa and the Middle Eastern states coexisted in the Bandung Movement; they journeyed together to the United Nations General Assembly, but up until the mid-1970’s closer bonds, which resulted in the greater coordination of policies on major international issues, did not develop. In fact prior to the 1973 massive defection of African states from the Israeli camp, most of the independent African states were locked in diplomatic and political embrace with the Jewish state. Indeed, Africa was unique in the sense that it was the only part of the Afro-Asian world where the Israelis received warm welcome. Israeli leaders tried hard to win friends and influence people in Asia but without success. It is indeed against this background that the present book can be adequately reviewed. The work consists of the proceedings of a major conference held in Amman, Jordan on 24-29 April, 1983. Organized by the Centre for Arab Unity Studies, it brought together some sixty participants. Though the conference itself was conducted in Arabic, many of the participants suggested that the proceedings be published in English and French. This book is the English ...